Vaginal Birth After Cesarean Characteristics with Maternal and Perinatal Out Come in Sanglah Hospital, Bali, 1st January 2015 to 31st December 2016 Period:A Descriptive Study - I Ketut Surya Negara; Gede Agus Hendra Sujana (Journal of Global Pharma Technology, 2017)
Cesarean section delivery is a common choice for some women because it is often considered faster and safer. Over the past few decades, the cesarean section continues to be performed more frequently. As a result, there is also an increase in the number of women with a history of cesarean section and become a problem for pregnancy and subsequent types of labor. Method This is a retrospective descriptive study obtained using medical records in Sanglah Hospital Bali, 1st January 2015 to 31st December 2016 Period. Results Within 2 years since January 1, 2015 - December 31, 2016, the number of births in Single Deposer hospital as many as 2502 cases, consisting of 1753 (70.06%) vaginal delivery and 749 (29.94%) with cesarean section. Of all deliveries, the total number of deliveries with uterine scarring were 247 cases, consisting of 190 (76.92%) of direct cases of cesarean section, and 57 (23.08%) cases were decided by TOLAC. Of 57 TOLAC cases, 49 cases were successful VBAC (85.96%), while 8 cases were unsuccessful VBAC (14.04%).The incidence of VBAC was most frequently found in the age group of 20-35 years old (82.46%), body mass index (BMI) of ≤30 kg/m2 (91.23%), and gestational age of ≤40 weeks (84.2%). Based on the number of previous vaginal deliveries after cesarean, women with a history of vaginal delivery was most common with 29 cases. Based on previous cesarean section indications, fetal distress had the highest number of cases (35.09%). Women with cervix dilatation of ≥4 cm are more likely to have successful VBAC (85.96%). Almost all VBAC was spontaneous vaginal delivery (97.96%), except one. Almost all newborn have a birth weight of less than 4 kg (98.25%). Anemia and hysterectomy are among maternal morbidities found in our study. Based on perinatal morbidity, asphyxia, neonatal dengue, ARDS, and jaundice, were found in our study and only four newborns needed to be treated in the neonatal intensive care unit (NICU). Conclusion The success rate of VBAC in this study was high, the indications of previous cesarean section most due to fetal distress. Moderate asphyxia was the most common perinatal morbidity, followed by ARDS, severe asphyxia, neonatal dengue and jaundice. However, in most cases there is no perinatal morbidity. Keyword: Vbac, Tolac, Maternal Perinatal Outcome.